1983
DOI: 10.1530/jrf.0.0690693
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical demonstration of relaxin in the genital tract of men

Abstract: Summary. The biotin\p=n-\avidinimmunoperoxidase staining method and antisera against highly purified porcine relaxin were utilized to localize relaxin in the male genital tract. Formalin-fixed tissue specimens from the prostate gland, the testis, epididymis, vas deferens and the seminal vesicle were studied. Specific relaxin immunoactivity was seen in the glandular epithelium of the prostate and also in the glandular epithelium of the seminal vesicle and in the ampullary part of the vas deferens. The testis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…Unlike its effects on body growth, the finding that relaxin regulates the male reproductive tract confirms the findings of earlier investigations that demonstrated male reproductive tissues as being targets for relaxin activity (Brenner et al, 1984;Carrell et al, 1995;Essig et al, 1982;Ivell et al, 1989;Min and Sherwood, 1998;Weiss, 1989;Winslow et al, 1992;Yki-Jarvinen et al, 1983). Relaxin was previously identified in the seminal plasma of humans (Weiss, 1989;Winslow et al, 1992) in the peripheral circulation of boars (Juang et al, 1996) and was shown to enhance the penetration of human sperm into human or bovine cervical mucus (Brenner et al, 1984).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Unlike its effects on body growth, the finding that relaxin regulates the male reproductive tract confirms the findings of earlier investigations that demonstrated male reproductive tissues as being targets for relaxin activity (Brenner et al, 1984;Carrell et al, 1995;Essig et al, 1982;Ivell et al, 1989;Min and Sherwood, 1998;Weiss, 1989;Winslow et al, 1992;Yki-Jarvinen et al, 1983). Relaxin was previously identified in the seminal plasma of humans (Weiss, 1989;Winslow et al, 1992) in the peripheral circulation of boars (Juang et al, 1996) and was shown to enhance the penetration of human sperm into human or bovine cervical mucus (Brenner et al, 1984).…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, reports of additional actions of relaxin in tissues (Tan et al, 1999) and cells (Parsell et al, 1996;Unemori and Amento, 1990;Wyatt et al, 2002) outside the female reproductive tract and the localization of relaxin binding sites in the heart and brain (Osheroff et al, 1992;Osheroff and Ho, 1993;Osheroff and Phillips, 1991) have expanded the role of relaxin from a hormone of pregnancy to a growth factor/cytokine. Immunoreactive relaxin and relaxin-binding sites have also been detected within the male reproductive tract: in the prostate (Ivell et al, 1989;Yki-Jarvinen et al, 1983), the seminal fluid (Essig et al, 1982;Weiss et al, 1986;Winslow et al, 1992), testis (Min and Sherwood, 1998), and spermatozoa (Carrell et al, 1995). In contrast to mammals where relaxin is produced in the prostate (Ivell et al, 1989;Yki-Jarvinen et al, 1983), the testis appears to be the major source of relaxin in some species (Steinetz et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm an increased expression of relaxin at the protein level in cancer cells, we analyzed the expression of relaxin protein in tissue microarrays by immunohistochemistry using a specific antihuman RLN2 antibody (22). Relaxin expression was present in both normal glandular epithelial cells and cancer cells as reported previously (5,6). However, there was significant Fig.…”
Section: Resultsmentioning
confidence: 54%
“…In most species, the prostate is the main source of the hormone (reviewed in Sherwood (1994Sherwood ( , 2004). In humans, the relaxin gene and protein are expressed in the prostate (Sokol et al 1989, Gunnersen et al 1996, Garibay-Tupas et al 2000, but relaxin immunoreactivity is also present in the seminal vesicles and the ampular region of the vas deferens (Yki-Järvinen et al 1983). In the boar, the seminal vesicle seems to be the main source of the hormone (Kohsaka et al 1992), although a relaxin-like antigen may also be present in the testis (Dubois & Dacheux 1978).…”
Section: Introductionmentioning
confidence: 99%